Revitalisasi Kelompok Wanita Nelayan (KWN) "Mandiri" Melalui Optimalisasi Digital Marketing dan Standarisasi Produk Terasi Di Desa Sungai Undang Kabupaten Seruyan - Rokhman Permadi; Lili Winarti; Sari Hayati; Sigit Mulyanto (I-Com: Indonesian Community Journal, 2024)
This Community Service Program (PKM) aims to enhance the production capacity, marketing, and business management of the "Mandiri" Fisherwomen Group (KWN) in Sungai Undang Village through the application of digital marketing and the standardization of shrimp paste products. The activities included training on packaging design, online marketing, financial bookkeeping using Android-based applications, and assistance in obtaining business permits such as NIB, PIRT, and Halal certification. As a result, KWN "Mandiri" members demonstrated significant improvements in their business management skills, with higher quality shrimp paste products and broader market reach. The acquired legal permits have opened up access to wider markets, while the entrepreneurial motivation instilled has strengthened the members' drive to develop their business. This program successfully empowered KWN "Mandiri" to compete in more competitive markets, enhancing their welfare and making a positive contribution to the local economy.